Three-Dimensional Power Doppler Ultrasonography for Diagnosing Abnormally Invasive Placenta and Quantifying the Risk - Collins, Sally L. (Obstet Gynecol, 2015)
OBJECTIVE: To test an objective ultrasound marker for diagnosing the presence and severity of abnormally invasive placenta. METHODS: Women at risk of abnormally invasive placenta underwent a three-dimensional power Doppler ultrasound scan. The volumes were examined offline by a blinded observer. The largest area of confluent three-dimensional power Doppler signal (Area of Confluence [A(con)], cm(2)) at the uteroplacental interface was measured and compared in women subsequently diagnosed with abnormally invasive placenta and women in a control group who did not have abnormally invasive placenta. Receiver operating characteristic curves were plotted for prediction of abnormally invasive placenta and abnormally invasive placenta requiring cesarean hysterectomy. RESULTS: Ninety-three women were recruited. Results were available for 89. Abnormally invasive placenta was clinically diagnosed in 42 women;36 required hysterectomy and had abnormally invasive placenta confirmed histopathologically. Median and interquartile range for A(con) was greater for abnormally invasive placenta (44.2 [31.4–61.7] cm(2)) compared with women in the control group (4.5 cm(2) [2.9–6.6], P<.001) and even greater in the 36 requiring hysterectomy (46.6 cm(2) [37.2–72.6], P<.001). A(con) rose with histopathologic diagnosis: focal accreta (32.2 cm(2) [17.2–57.3]), accreta (59.6 cm(2) [40.1–89.9]), and percreta (46.6 cm(2) [37.5–71.5]; P<.001 analysis of variance for linear trend). Receiver operating characteristic analysis for prediction of abnormally invasive placenta revealed that with an A(con) of 12.4 cm(2) or greater, 100% sensitivity (95% confidence interval [CI] 91.6–100) could be obtained with 92% specificity (95% CI 79.6–97.6); area under the curve is 0.99 (95% CI 0.94–1.0). For prediction of abnormally invasive placenta requiring hysterectomy, 100% sensitivity (95% CI 90.3–100) can be obtained with an A(con) of 17.4 cm(2) or greater with 87% specificity (95% CI 74.7–94.5; area under the curve 0.98 [0.93–1.0]). CONCLUSION: The marker A(con) provides a quantitative means for diagnosing abnormally invasive placenta and assessing severity. If further validated, subjectivity could be eliminated from the diagnosis of abnormally invasive placenta.